Femtosecond Pulsed Laser Irradiation of Zirconia for Embedding Silver Nanoparticles in Surface Nanopores - Yuka Yamamuro; Tomotaka Shimoyama; Hiroya Nagata; Jiwang Yan (Applied Sciences, 2023)
Femtosecond pulsed laser irradiation was performed to investigate the feasibility and fundamental characteristics of embedding silver nanoparticles onto zirconia ceramic surfaces. By irradiating laser, nanopores were fabricated on the surface of the yttria-stabilized zirconia (YSZ) substrate, and silver nanoparticles were infiltrated and immobilized into the pores using a commercial nano-silver dispersion solution. Numerous nanopores embedded with silver nanoparticles were successfully obtained on the YSZ surface while keeping the grains’ shapes unchanged by controlling laser parameters. Optimizing laser fluence and scanning speed near the ablation threshold made it possible to remove only the excess dispersant that remained on the surface while keeping silver in the pores and without causing machining of the surface of the YSZ substrate. In addition, about 60% embedding in the nanopores was achieved. It was found that the shorter pulse width was suitable to avoid evaporating both dispersant and silver. Cross-sectional observation revealed that the silver nanoparticles were agglomerated to form clumps and were embedded without a gap at the bottom of the pores at a depth of about 600 nm. After laser irradiation, no significant laser-induced phase change was observed in the YSZ substrate, indicating that there was no in-process thermal damage to the bulk. These findings demonstrated the possibility of adding a metal nanoparticle to the zirconia surface by using only a laser process without damaging the properties of the base material during the process. New applications of zirconia, such as the generation of functional surfaces with antibacterial properties, are expected.